Have restricted working hours reduced junior doctors' experience of fatigue? A focus group and telephone interview study. Issue 3 (6th March 2014) - Morrow, Gill; Burford, Bryan; Carter, Madeline; Illing, Jan
Abstract : Objective: To explore the effects of the UK Working Time Regulations (WTR) on trainee doctors' experience of fatigue. Design: Qualitative study involving focus groups and telephone interviews, conducted in Spring 2012 with doctors purposively selected from Foundation and specialty training. Final compliance with a 48 h/week limit had been required for trainee doctors since August 2009. Framework analysis of data. Setting: 9 deaneries in all four UK nations; secondary care. Participants: 82 doctors: 53 Foundation trainees and 29 specialty trainees. 36 participants were male and 46 female. Specialty trainees were from a wide range of medical and surgical specialties, and psychiatry. Results: Implementation of the WTR, while acknowledged as an improvement to the earlier situation of prolonged excessive hours, has not wholly overcome experience of long working hours and fatigue. Fatigue did not only arise from the hours that were scheduled, but also from an unpredictable mixture of shifts, work intensity (which often resulted in educational tasks being taken home) and inadequate rest. Fatigue was also caused by trainees working beyond their scheduled hours, for reasons such as task completion, accessing additional educational opportunities beyond scheduled hours and staffing shortages. There were also organisational, professional and cultural drivers, such as a sense of responsibility to patients and colleagues and the expectations of seniors. Fatigue was perceived to affect efficiency of skills and judgement, mood and learning capacity. Conclusions: Long-term risks of continued stress and fatigue, for doctors and for the effective delivery of a healthcare service, should not be ignored. Current monitoring processes do not reflect doctors' true working patterns. The effectiveness of the WTR cannot be considered in isolation from the culture and context of the workplace. On-going attention needs to be paid to broader cultural issues, including the relationship between trainees and seniors.